2019
DOI: 10.1093/ecco-jcc/jjz051
|View full text |Cite|
|
Sign up to set email alerts
|

European Crohn’s and Colitis Organisation Topical Review on Complementary Medicine and Psychotherapy in Inflammatory Bowel Disease

Abstract: Patients with inflammatory bowel disease [IBD] increasingly use alternative and complementary therapies, for which appropriate evidence is often lacking. It is estimated that up to half of all patients with IBD use various forms of complementary and alternative medicine during some point in their disease course. Considering the frequent use of such therapies, it is crucial that physicians and patients are informed about their efficacy and safety in order to provide guidance and evidence-based advice. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
2
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 210 publications
(267 reference statements)
2
90
2
13
Order By: Relevance
“…IBD treatment with these drugs is inherently burdened by some degree of immunosuppression and by a greater likelihood of infections, although there does not seem to be a strong association between the occurrence of infections and biological drug dose 12,13 . This notwithstanding, patients with IBD are often concerned regarding the potential for the occurrence of immunosuppression‐related events, and in general, in patients with IBD, the occurrence of stressor events may represent a trigger for disease relapse 14 …”
Section: Research Lettermentioning
confidence: 99%
“…IBD treatment with these drugs is inherently burdened by some degree of immunosuppression and by a greater likelihood of infections, although there does not seem to be a strong association between the occurrence of infections and biological drug dose 12,13 . This notwithstanding, patients with IBD are often concerned regarding the potential for the occurrence of immunosuppression‐related events, and in general, in patients with IBD, the occurrence of stressor events may represent a trigger for disease relapse 14 …”
Section: Research Lettermentioning
confidence: 99%
“…One of the most studied conditions in gastroenterology field, IBD is a set of chronic disorders that affects the digestive tract and includes Crohn's disease (CD) and ulcerative colitis (UC)[ 11 ]. Although the mechanisms involved in IBD genesis are broadly studied, they are not well understood and may include genetic, immune, and environmental interactions[ 12 ].…”
Section: Extragastric Manifestationsmentioning
confidence: 99%
“…The European Crohn's and Colitis Organization (ECCO) recently published a Topical Review on Complementary Medicine and Psychotherapy in Inflammatory Bowel Disease and provided clinical guidance based on the current available evidence. 99 They outlined that curcumin, in combination with 5-ASA, may be effective in inducing remission in mild-to-moderate UC as well as potentially being effective as a complementary maintenance therapy in UC. They concluded that omega-3 fatty acids may be beneficial in maintaining remission in Crohn's disease; however, study quality and heterogeneity of trials limit these findings.…”
Section: Clinical Guidelinesmentioning
confidence: 99%